Shear Bond Strengths of Different Adhesive Systems to Biodentine - Mesut Enes Odabaş; Mehmet Bani; Resmiye Ebru Tirali (The Scientific World Journal)
The aim of this study was to measure the shear bond strength of different adhesive systems to Biodentine with different time intervals. Eighty specimens of Biodentine were prepared and divided into 8 groups. After 12 minutes, 40 samples were randomly selected and divided into 4 groups of 10 each: group 1: (etch-and-rinse adhesive system) Prime & Bond NT; group 2: (2-step self-etch adhesive system) Clearfil SE Bond; group 3: (1-step self-etch adhesive systems) Clearfil S3 Bond; group 4: control (no adhesive). After the application of adhesive systems, composite resin was applied over Biodentine. This procedure was repeated 24 hours after mixing additional 40 samples, respectively. Shear bond strengths were measured using a universal testing machine, and the data were subjected to 1-way analysis of variance and Scheffé post hoc test. No significant differences were found between all of the adhesive groups at the same time intervals (12 minutes and 24 hours) (). Among the two time intervals, the lowest value was obtained for group 1 (etch-and-rinse adhesive) at a 12-minute period, and the highest was obtained for group 2 (two-step self-etch adhesive) at a 24-hour period. The placement of composite resin used with self-etch adhesive systems over Biodentine showed better shear bond strength.